TAVI in Africa - Destined for the townships or dashing for the “ivory towers”? - Doubell, Anton (SA Heart Journal, 2017)
Few treatments in the field of cardiology are more established than surgical aortic valve replacement for symptomatic severe aortic stenosis. It is estimated that over a million of these procedures have been performed since the first implant half a century ago and a 30-day mortality of less than 4% is often quoted. Although randomised trials comparing aortic valve replacement to optimal medical treatment for aortic stenosis have never been done, actuarial survival curves comparing valve replacement to medical therapy alone and medical therapy including balloon valvuloplasty (not followed by valve replacement) clearly established the benefit of valve replacement.